Agricultural market reforms in Egypt: initial adjustments in local input markets - Goletti, Francesco (International Food Policy Research Institute, 1994)
The high use of modern inputs in Egypt's agricultural system well before the reforms has been very favorable to the development of private markets, particularly in the fertilizer sector. The level of adoption being very high, the usual demand constraints did not operate and traders' entry was facilitated by the size of the market....In the fertilizer sector, the reduction in subsidies has been initially accompanied by a reduction in use, but by 1993 fertilizer use has returned to its 1991 levels...The effect on crop production has been positive in most cases, with increases in production and yields. Higher nominal prices of fertilizers and pesticides did not translate into higher real prices. There is some evidence that the ratio between foodgrain prices and the prices of fertilizers, pesticides, and labor have gone up, pointing indirectly to some evidence concerning improvement in average farmer's income, to the extent that changes in the cost of other inputs like land and equipment do not exceed these gains.